Data Collection Procedures and Injury Definitions in Badminton: A Consensus Statement According to the Delphi Approach. - Gijón-Noguerón, Gabriel; Ortega-Ávila, Ana Belén; Kaldau, Niels Christian; Fahlstrom, Martin; Felder, Hano; Kerr, Stewart; King, Mark; McCaig, Steve; Marchena-Rodríguez, Ana José; Cabello-Manrique, David (Lippincott, Williams & Wilkins, 2022)
Previous studies involving injury surveillance in badminton players have used non-standardized injury definitions and data collection methodologies. The purpose of this study was to apply a Delphi method to (1) reach a consensus on an injury definition in badminton and (2) develop a standardized badminton injury report form. An Injury Consensus Group was established under the auspices of the Badminton World Federation, and initial injury definitions and injury report form were developed. An internal panel was formed from the Injury Consensus Group, and an external panel was selected based on a combination of profession, experience in the field, sport-specific knowledge/expertise, and geographical location to obtain a widely representative sample. Through 2 rounds of voting by the external panel, consensus was reached on both the definition of an injury in badminton and a standardized injury report form. The agreed injury definition was “Any physical injury sustained by a player during a match or training regardless if further diagnostic tests were done or if playing time was lost” and the injury report form contained the following 7 sections: Injury record, Diagnosis, Injury mechanism, Regarding pain, Pain and return to play/training after injury, Grade of severity, and Recurrence. We recommend the use of the definitions and methods presented in this consensus statement for the reporting of injury in all international and domestic badminton players. This should make future injury surveillance reports directly comparable and hence more informative in recognizing trends over time and differences between countries.
https://openpolicyfinder.jisc.ac.uk/id/publication/8742
Keywords: Lesiones deportivas; Jugadores de bádminton - Heridas y lesiones; Epidemiología; Badminton; Injury; Consensus; Epidemiologic studies